Low Serum Fetuin-A as a Biomarker to Predict Pneumococcal Necrotizing Pneumonia and Hemolytic Uremic Syndrome in Children. Issue 13 (March 2016) - Janapatla, Rajendra Prasad; Hsu, Mei-Hua; Liao, Wan-Ting; Chien, Kun-Yi; Lee, Hao-Yuan; Chiu, Cheng-Hsun
Abstract : Abstract: Streptococcus pneumoniae, a neuraminidase-producing pathogen, can cause invasive pneumococcal disease (IPD) with or without hemolytic uremic syndrome (HUS) in humans. We aimed to identify serum sialoglycoproteins that are targeted by neuraminidases in severe pneumococcal infection. We hypothesized that serum sialoglycoprotein such as fetuin-A can serve as a biomarker to predict IPD or HUS. We constructed serum sialoglycoprotein profiles before and after pneumococcal neuraminidase treatment using liquid chromatography-tandem mass spectrometry (LC-MS/MS), a proteomic approach. An observational study was conducted using clinical data and serum samples from pediatric patients with pneumococcal infection to verify the predictive role of fetuin-A in IPD. Serum fetuin-A levels were determined by enzyme-linked immunosorbent assay. The most abundant serum sialoglycoproteins identified by LC-MS/MS after neuraminidase treatment and peanut lectin capture were immunoglobulins, apolipoproteins, fibrinogens, keratins, complement system proteins, and fetuin-A. Serum fetuin-A levels in the HUS patients were significantly lower (207 ± 80 mg/L, P < 0.001) than in patients with lobar pneumonia (610 ± 190 mg/L) as well as the healthy controls (630 ± 250 mg/L). In comparing HUS with necrotizing pneumonia and lobar pneumonia, the ROC area under the curve was 0.842; a cutoff value of 298 mg/L yielded sensitivity of 92.9% (95% CI: 68.5–98.7%) and specificity of 71.9% (95% CI: 54.6–84.4%). This observational study with validation cohorts of patients with HUS, complicated pneumonia, and lobar pneumonia demonstrates the high performance of low serum fetuin-A levels as a biomarker to predict severe IPD and HUS in children.